Simplified procedure for structural integrity's evaluation of monuments in constrained context: The case of a Buddhist Temple in Bagan (Myanmar). - Russo, Salvatore (Journal of Cultural Heritage, 2017)
The research focuses exclusively on a simplified non-destructive testing procedure for first estimating structural integrity of monuments in constrained frame determined by emergency switchboard, need of rapidity, absence of economic support and complexity of the site and environment. The survey was inspired by the experimental outcomes obtained through easy-bring devices applied on a very old Buddhist Temple in Bagan (Myanmar) – whose area is UNESCO's site – built in the XII century. The ductile devices used for the investigation are the rebound hammer, the endoscopy and the ultra-sonic test. The procedure has been applied locally in the more significant masonry bearing parts of the temple. Particularly attention has been paid on the evaluation of the compression strength of brick and on the brick-mortar joints efficiency. The survey's approach is rapid, strictly in the frame of a preliminary and limited characterization, but significant for a first understanding of the masonry's integrity in absence of dedicated and elevated resources. The study outlines the reliability/limitations of the simplified and poor investigation's procedure in constrained boundary conditions, which is a very common situation in the anamnesis and diagnosis phases of monuments before restoration.